Sex differences in brain metabolites in anxiety and mood disorders. (30th November 2020) - Pigoni, Alessandro; Delvecchio, Giuseppe; Squarcina, Letizia; Bonivento, Carolina; Girardi, Paolo; Finos, Livio; Crisanti, Camilla; Balestrieri, Matteo; D'Agostini, Serena; Stanley, Jeffrey A.; Brambilla, Paolo
Highlights: Gender differences have been found in depression and anxiety disorders. The neural basis of gender differences in depression/anxiety disorders are unclear. Male with PD and GAD had lower GPC+PC and glutamate levels compared to controls. An association between gender and brain metabolites was shown in anxiety spectrum. Abstract: Gender differences in mood and anxiety disorders are well-established. However, the neural basis of these differences is not clear yet, especially in terms of brain metabolism. Indeed, although several proton Magnetic Resonance Spectroscopy (¹H MRS) investigations reported different metabolic levels in both depression and anxiety disorders, which have been also linked to symptoms severity and response to treatment, the role of gender on these differences have not been explored yet. Therefore, this study aims at investigating the role of sex in neurometabolic alterations associated with both mood and anxiety disorders. A 3T single-voxel ¹H MRS acquisition of the dorsolateral prefrontal cortex was acquired from 14 Major Depressive Disorder, 10 Generalized Anxiety Disorder (GAD), 11 Panic Disorder (PD), patients and 16 healthy controls (HC). Among males, PD patients showed significantly lower GPC+PC (also observed in GAD+PD) and Glu levels compared to HC. Finally, a significant group x sex interaction effect was observed in the GPC+PC and Glu levels. We proved the presence of an association between sex and brain metabolites in anxiety spectrum.